Performance, growth and earnings management - LEE, Chi Wen Jevons (Institutional Knowledge at Singapore Management University, 2006)
We study the relationship between the amount of managed earnings and firms' earnings performance and expected growth in a reporting model, where managers manipulate earnings to influence the valuation of firms' equity while bearing a cost that is increasing and convex in the amount of managed earnings. In the unique revealing equilibrium to the model, firms with higher performance and growth over-report earnings by a larger amount because price responsiveness increases with earnings performance and growth. And earnings quality, defined as the proportion of true economic earnings in total reported earnings, increases with earnings performance but decreases with earnings growth. We conduct empirical tests on a large sample and a restatement sample using different proxies for earnings management. Results from the large sample tests support our predictions while results from the restatement sample tests are mixed. Our study provides an alternative explanation to the positive relationship between discretionary accruals estimated from the Jones model and firms' performance and growth.